1992
DOI: 10.1007/bf02221680
|View full text |Cite
|
Sign up to set email alerts
|

A nationwide cross-sectional study of retinopathy and microalbuminuria in young Norwegian Type 1 (insulin-dependent) diabetic patients

Abstract: A nationwide cohort of Type 1 (insulin-dependent) diabetic patients was studied to determine the prevalence of retinopathy and microalbuminuria and to evaluate the association to various risk factors. Of 600 subjects with mean age of 19.8 years (range 8.0-30.3) and a mean duration of diabetes of 10.5 years (range 6.2-17.3), 371 (60%) volunteered for a clinical examination which included fundus photography, timed overnight urine samples for albumin excretion rate, measurement of arterial blood pressure and dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
46
2
3

Year Published

1997
1997
2009
2009

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 90 publications
(60 citation statements)
references
References 37 publications
(34 reference statements)
9
46
2
3
Order By: Relevance
“…In 1989, 600 randomly selected patients among the 1,868 who were alive and still living in Norway were invited to a clinical examination for assessment of diabetic complications as previously reported [15]. Of the 368 subjects who participated in the baseline examination between 1989 and 1990, 355 were eligible for a follow-up examination in the years 2002 to 2003.…”
Section: Patientsmentioning
confidence: 99%
See 4 more Smart Citations
“…In 1989, 600 randomly selected patients among the 1,868 who were alive and still living in Norway were invited to a clinical examination for assessment of diabetic complications as previously reported [15]. Of the 368 subjects who participated in the baseline examination between 1989 and 1990, 355 were eligible for a follow-up examination in the years 2002 to 2003.…”
Section: Patientsmentioning
confidence: 99%
“…The total risk in the full cohort of participants and non-participants is a weighted average of the Data from non-participants in the examination in 1990 indicated that the mean HbA 1c was 9.5% among nonparticipants compared with 8.9% among participants [15], i.e. a difference of 0.6%.…”
Section: Sensitivity Analysis Of Non-participationmentioning
confidence: 99%
See 3 more Smart Citations